REPRESENTASI ASPEK PSIKOLOGI PADA PUISI KENANGAN DAN KESEPIAN KARYA W.S RENDRA: KAJIAN TIPOLOGI CARL JUNG - Ali, Ayu Hidayanti; Nasiru, La Ode Gusman; Mulusi, Mirna M.; Nurdin, Nuryana (Jurnal Bahasa, Sastra, dan Budaya, 2024)
This study reveals the representation of psychological aspects in the poem "Kenangan dan Kesepian" by W.S. Rendra through Carl Gustav Jung's psychoanalytic approach, especially within the framework of personality typology. Poetry as a form of literary work is often a medium to express the author's inner experiences and emotions. The method used in this study is descriptive analysis with a focus on Jung's personality system which includes consciousness, unconsciousness, attitude, and soul function, especially the function of feelings. The results of the analysis show that the poem reflects the poet's introverted personality, namely expressing longing, loneliness, and contemplation of past memories through melancholic symbols and images.